1989
DOI: 10.1037/0022-0167.36.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Psychological symptoms of counseling center clients.

Abstract: This study provides descriptive data concerning type and severity of psychological symptoms of counseling center clients. Of 1,928 university students counseled during a 1-year period, 1,589 (82.4%) completed the Symptom Check List-90-Revised (SCL-90-R) at the time of initial contact. Women (n = 1,004) reported more severe symptomatology than did men (« = 585). On the basis of adolescent norms, which suggested less psychopathology than did adult norms, at least one fourth of all clients obtained scores indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
33
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 17 publications
6
33
0
Order By: Relevance
“…It is interesting to note that the percentage of students considered to be psychologically disturbed in the Johnson et al (1989) study decreased to about one fourth of the sample when compared with adolescent nonpatient rather than adult norms. This finding provides additional support for the point made earlier in this article, that is, that certain types of problems can be viewed as more developmental rather than pathological in nature when age is accounted for.…”
Section: Review Of Researchmentioning
confidence: 89%
See 2 more Smart Citations
“…It is interesting to note that the percentage of students considered to be psychologically disturbed in the Johnson et al (1989) study decreased to about one fourth of the sample when compared with adolescent nonpatient rather than adult norms. This finding provides additional support for the point made earlier in this article, that is, that certain types of problems can be viewed as more developmental rather than pathological in nature when age is accounted for.…”
Section: Review Of Researchmentioning
confidence: 89%
“…Thus, there is research evidence to suggest that serious forms of psychopathology are not uncommon in counseling center clients. For example, in a sample of 1,589 students who entered counseling during a l-year period, Johnson et. al.…”
Section: Review Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 6 -8 years is a relatively short time in which to look for long-term changes in client problems. Other researchers have found high overall scores in client distress at intake (Todd, Dean, & McKenna, 1997;Johnson, Ellison, & Heikkinen, 1989). Relatively high overall distress levels at intake may have differed from the therapists' perceptions of severity and client problems over the course of therapy.…”
mentioning
confidence: 95%
“…In her literature review, Waddell (1998) found either no link or an unclear link between creativity and psychopathology in 20 of the 29 studies reviewed. Similarly, other studies have found that students at traditional colleges and universities also have distress scores that approach those of psychiatric outpatient clients (Gitlin & McGuff, 1995;Heppner et al, 1994;Johnson, Ellison, & Heikkinen, 1989), suggesting that the psychological distress of art-student counseling-center clients is no more severe than the distress of nonartist students seeking counseling. Despite similarities in reported psychological symptoms, the study did find that student artists experience more perceived stress than traditional students.…”
Section: Psychological Symptomsmentioning
confidence: 93%